CREATING WORLD CLASS UNIVERSITY FOR HIGHER EDUCATIONAL INSTITUTION IN INDONESIA: GOVERNANCE POLICIES AND CHALLENGES - Anisyah, Siti; Alfitri, Alfitri; Lionardo, Andries; Thamarin, Muhammad Husni (Jurnal EL-RIYASAH, 2025)
The World Class University (WCU) agenda has become a strategic issue in the development of global higher education, including in Indonesia. The government has consistently encouraged universities, both State Universities (PTN) and State Islamic Universities (PTKIN), to increase their international competitiveness through regulatory policies, publication incentive programs, and institutional internationalization. This study uses a literature review approach with a qualitative meta-analysis method to identify WCU strategies, challenges, and opportunities in Indonesia. The results show that despite a significant increase in the number of international publications, academic collaboration, and global recognition of Indonesian universities, there is still a considerable gap between policy ambitions and implementation realities. The main inhibiting factors include weak governance transparency, political intervention, limited research budgets, low lecturer qualifications, and an internationalization orientation that is more instrumental than substantive. On the other hand, the successes of other countries, such as Malaysia with its publication incentive policy, Singapore through national policy integration, and India, which faces access inequalities, provide important lessons for Indonesia. These findings emphasize the need for a reflective internationalization strategy, rooted in local values and supported by collective leadership and the use of digital technology. Thus, achieving WCU status is not only about fulfilling global indicators, but also about building adaptive governance, strengthening a culture of research, and reinforcing Indonesia's academic identity on the global stage.